Gisting as a Colonial Agrarian Frontier: Indo-European Settlement and Social Engineering, 1926–1942 - Ajeng Diah Kinanti; Ririn Darini; Wildhan Ichzha Maulana (Diakronika, 2026)
Indo-Europeans, as a marginalised group, fought for their rights to education and fair wages through the moderate IEV organisation, which supported Dutch colonial government policies. This study examines Indo-European agricultural colonisation in Gisting as an instrument of the colonial government for social and agrarian control. The method used is historical, with four stages: heuristic process, verification, interpretation, and historiography. The results of the study show that (1) The success of Gisting's agricultural colonization as a tool to strengthen colonial domination over the region and agrarian resources and to form an independent community loyal to colonial power (2) The colonization of Gisting tested Indo-European solidarity not only in terms of social experimentation but also in terms of the stake of Indo-European dignity amid the ambitions of the colonial government. (3) The transformation of the Gisting landscape not only turned forests into coffee plantations but also led to economic competition and the emergence of Javanese coolies, which made the Indo-Europeans in Gisting small landlords. For the colonial government, the colonisation of Java was a strategic way to manage Indo-European conflicts in Java while opening up economic opportunities with shared financial burdens. Still, the physical risks and dignity were entirely borne by the Indo-Europeans, so that the colonisation of Gisting can be described as an unequal mutualistic symbiosis.